Analysis of Mangrove Forest Changes Using Satellite Image Data on Rupat Island - Agusti, Dinda Roanna; Mubarak, Mubarak; Efriyeldi, Efriyeldi; Rifardi, Rifardi; Mulyadi, Aras; Zulkifli, Zulkifli; Ilahi, Ilham (Jurnal Natur Indonesia, 2025)
Mangrove forest vegetation is spread across several islands in Indonesia, including Rupat Island. Rupat Island is the outermost island in Riau Province, close to Malaysia, and directly faces international waters, namely the Malacca Strait. Rupat Island has two sub-districts, namely Rupat District and North Rupat District. Rupat Island has a very extensive mangrove forest and has a significant contribution. Monitoring changes in mangrove forests is one way of controlling the mangrove forest ecosystem. This research aims to analyze changes in mangrove vegetation area and mangrove density using the MVI algorithm in 2013 and 2023 on Rupat Island, Bengkalis Regency. This research was conducted in the mangrove forest ecosystem on Rupat Island, Bengkalis Regency, Riau Province. The method used in this research is a survey method with observation and field data collection (ground check). Based on image processing results, the area of ​​mangrove vegetation was 13903.03 ha (2013) to 11748.66 ha (2023) and experienced a reduction of 2154.37 ha. Classification based on MVI in sparse density has an area of ​​5872.46 ha (2013), decreasing to 3422.05 ha (2023); medium density has an area of ​​2188.84 ha (2013), increasing to 3334.64 ha (2023), and dense density has an area of ​​5841.73 ha (2013) reduced to 4991.97 ha. Over 10 years, the density of mangrove vegetation has increased in the medium class and tends to decrease in the sparse and dense classes. Based on calculations, the density of mangroves on Rupat Island falls into the tree category, ranging from 1150.00 ind/ha to 1450.00 ind/ha, which is considered good, and the sapling category ranges from 366.67 ind/ha to 1050.00 ind/ha, which is classified as good.